Effect of magnetic field on peristaltic flow of Walters B fluid through a porous medium in a tapered asymmetric channel. (JOURNAL OF ADVANCES IN MATHEMATICS, 2017)
The problem of peristaltic transport of an incompressible non-Newtonian fluid in a tapered a symmetric channel through a porous medium is presented under long-wave length and low Reynolds number assumptions, the fluid is considered to be Walters B fluid and electrically conducting by a transverse magnetic field.The tapered asymmetric channel in the flow induced by talking peristaltic wave imposed on the non-uniform boundary walls to possess different amplitudes and phases. Series solutions for stream function, axial velocity and pressure gradient are given using regular perturbation technique. Numerical computations have been performed for the pressure rise per wave length. The effect of the physical parameters of the problem on these distributions are discussed and illustrated graphically through a set of figures.